Inside Cover: Structure–Reactivity Relationship in the Frustrated Lewis Pair (FLP)‐Catalyzed Hydrogenation of Imines (Chem. Eur. J. 22/2016) - Tussing, Sebastian; Kaupmees, Karl; Paradies, Jan (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Recyclable Bifunctional Polystyrene and Silica Gel-Supported Organocatalyst for the Coupling of CO2with Epoxides - Kohrt, Christina; Werner, Thomas (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Scope and Limitation of the Microwave-Assisted Catalytic Wittig Reaction - Hoffmann, Marcel; Deshmukh, Sunetra; Werner, Thomas (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Recycling of Phosphorus-Based Organocatalysts by Organic Solvent Nanofiltration - Großeheilmann, Julia; Büttner, Hendrik; Kohrt, Christina; Kragl, Udo; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Phospholane-Catalyzed Wittig Reaction - Werner, Thomas; Hoffmann, Marcel; Deshmukh, Sunetra (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Synthesis of Cyclic Carbonates from Epoxides and Carbon Dioxide by Using Bifunctional One-Component Phosphorus-Based Organocatalysts - Büttner, Hendrik; Steinbauer, Johannes; Werner, Thomas (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

First Base-Free Catalytic Wittig Reaction - Schirmer, Marie-Luis; Adomeit, Sven; Werner, Thomas (Organic Letters)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry; Biochemistry

Crystal structure of diethyl (E)-2-[(benzofuran-2-yl)methylidene]succinate - Schirmer, Marie-Luis; Spannenberg, Anke; Werner, Thomas (Acta Crystallographica Section E Crystallographic Communications)
The title compound, C 17 H 18 O 5 , was synthesized by a base-free catalytic Wittig reaction. The molecule consists of a diethyl itaconate unit, which is connected via the C=C double bond to a benzofuran moiety. The benzofuran ring system (r.m.s. deviation = 0.007 Å) forms dihedral angles of 79.58 (4) and 12.12 (10)° with the mean planes through the cis and trans ethoxycarbonyl groups, respectively. An intramolecular C—H...O hydrogen bond involving the O atom of the benzofuran moiety is observed. In the crystal, molecules are linked into ribbons running parallel to the b axis by C—H...O hydrogen bonds.
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Highly Efficient Polymer-Supported Catalytic System for the Valorization of Carbon Dioxide - Desens, Willi; Kohrt, Christina; Frank, Marcus; Werner, Thomas (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Organocatalyzed Reduction of Tertiary Phosphine Oxides - Schirmer, Marie-Luis; Jopp, Stefan; Holz, Jens; Spannenberg, Anke; Werner, Thomas (Advanced Synthesis and Catalysis)
Keywords: General Chemistry

2-Hydroxyethylammonium iodide - Kohrt, Christina; Spannenberg, Anke; Werner, Thomas (Acta Crystallographica Section E Structure Reports Online)
In the crystal structure of the title salt, C 2 H 8 NO + ·I − , N—H...O, N—H...I and O—H...I hydrogen bonds lead to the formation of layers staggered along the c axis.
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

A Catalytic System for the Activation of Diorganozinc Reagents - Werner, Thomas; Bauer, Matthias; Riahi, Abdol Majid; Schramm, Heiko (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

First Microwave-Assisted Catalytic Wittig Reaction - Werner, Thomas; Hoffmann, Marcel; Deshmukh, Sunetra (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

First Enantioselective Catalytic Wittig Reaction - Werner, Thomas; Hoffmann, Marcel; Deshmukh, Sunetra (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Synthesis of cyclic carbonates from epoxides and CO2 catalyzed by potassium iodide and amino alcohols - Werner, Thomas; Tenhumberg, Nils (Journal of CO2 Utilization)
Keywords: Process Chemistry and Technology; Waste Management and Disposal; Chemical Engineering (miscellaneous)

Phosphorus-based Bifunctional Organocatalysts for the Addition of Carbon Dioxide and Epoxides - Werner, Thomas; Büttner, Hendrik (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Hydroxyl-Functionalized Imidazoles: Highly Active Additives for the Potassium Iodide-Catalyzed Synthesis of 1,3-Dioxolan-2-one Derivatives from Epoxides and Carbon Dioxide - Werner, Thomas; Tenhumberg, Nils; Büttner, Hendrik (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Bifunctional One-Component Catalysts for the Addition of Carbon Dioxide to Epoxides - Büttner, Hendrik; Lau, Kornelia; Spannenberg, Anke; Werner, Thomas (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Synthesis of mesoporous alumina through photo cross-linked poly(dimethylacrylamide) hydrogels - Birnbaum, Wolfgang; Weinberger, Christian; Schill, Verena; Haffer, Stefanie; Tiemann, Michael; Kuckling, Dirk (Colloid and Polymer Science)
Catalysis plays a central role in many fields of life, e.g., in biochemical processes, to reduce energy costs and resources in chemical industry and to decrease or even avoid environmental pollution and in energy management. Porous alumina (Al2O3) is an essential material in various applications, especially as a support material for catalysts. It is often prepared by nanocasting using porous carbon materials that serve as rigid structure matrices. In this work, an alternative way to synthesize mesoporous Al2O3 by using hydrogels as porogenic material is presented. Hydrogels can easily be patterned by light and used to imprint their structure onto alumina opening a new approach to fabricate patterned Al2O3. The hydrogels used in this work are based on poly(dimethylacrylamide) and were photo-chemically cross-linked. Followed by a nanocasting process, mesoporous alumina samples were synthesized and characterized by N2 physisorption and X-ray diffraction. The cross-linker amount in the polymer network was varied and the influence on the properties of the Al2O3 is analyzed.

X-ray Spectroscopic Verification of the Active Species in Iron-Catalyzed Cross-Coupling Reactions - Schoch, Roland; Desens, Willi; Werner, Thomas; Bauer, Matthias (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry